Protective effects of cilengitide on inflammation in chondrocytes under excessive mechanical stress. (6th January 2020) - Hirose, Naoto; Okamoto, Yuki; Yanoshita, Makoto; Asakawa, Yuki; Sumi, Chikako; Takano, Mami; Nishiyama, Sayuri; Su, Shao‐Ching; Mitsuyoshi, Tomomi; Kunimatsu, Ryo; Tanne, Kazuo; Tanimoto, Kotaro
Abstract: Chondrocytes constantly receive external stimuli, which regulates remodeling. An optimal level of mechanical stress is essential for maintaining chondrocyte homeostasis, however, excessive mechanical stress induces inflammatory cytokines and protease, such as matrix metalloproteinases (MMPs). Therefore, excessive mechanical stress is considered to be one of the main causes to cartilage destruction leading to osteoarthritis (OA). Integrins are well‐known as cell adhesion molecules and act as receptors for extracellular matrix (ECM), and are believed to control intracellular signaling pathways both physically and chemically as a mechanoreceptor. However, few studies have focused on the roles and functions of integrins in inflammation caused by excessive mechanical stress. In this study, we examined the relationship between integrins (αVβ3 and αVβ5) and the expression of inflammatory factors under mechanical loading in chondrocytes by using an integrin receptor antagonist (cilengitide). Cilengitide suppressed the gene expression of interleukin‐1β (IL‐1β), tumor necrosis factor‐α (TNF‐α), matrix metalloproteinase‐3 (MMP‐3), and MMP‐13 induced by excessive mechanical stress. In addition, the protein expression of IL1‐β and MMP‐13 was also inhibited by the addition of cilengitide. Next, we investigated the involvement of intracellular signaling pathways in stress‐induced integrin signaling in chondrocytes by using western blotting. The levels of p‐FAK, p‐ERK, p‐JNK, and p‐p38 were enhanced by excessive mechanical stress and the enhancement was suppressed by treatment with cilengitide. In conclusion, this study revealed that excessive mechanical stress may activate integrins αVβ3 and αVβ5 on the surface of chondrocytes and thereby induce an inflammatory reaction by upregulating the expression of IL‐1β, TNF‐α, MMP‐3, and MMP‐13 through phosphorylation of FAK and MAPKs.